Instant Coffee Acutely Affects Glucose Tolerance in University Students: Early Findings. (29th May 2020) - Rowlands, Tessa; Danhoff, Laura; Gainer, Bryce; Dolan, Kevin; Green, Natasha; Smith, Jenna; Thombs, Emma; Lowery, Lonnie
Abstract: Objectives: Coffee has been shown to enhance glucose disposal in middle-aged insulin-resistant subjects but less research has been done on healthy university students. We hypothesized that acute glucose disposal effects will be: Decaffeinated coffee > regular coffee > water in this population. Methods: Healthy participants ( N  = 10, 18–35 y, HbA1c  = 5.2%) of varied habitual coffee intakes were free of glycemia-affecting medications and were recreationally active. In a randomized, double-blind, crossover design, each pre-breakfast participant consumed Starbucks Via ® decaffeinated instant coffee (DCF), an identically tasting regular instant coffee (VIA), or water (WTR, unblinded) over 25 minutes. Subsequently, 48 g carbohydrate was provided as four pieces of commercial white bread. Whole blood glucose measures were taken in duplicate each 30 min. for two hours. Results: For glucose concentrations (mg/dl), a 3 × 5 repeated measures factorial ANOVA revealed a non-significant trend in the statistical interaction ( P  ≤ 0.10), with DCF quantitatively increasing the most at 30 minutes (150.4 ± 21.4 mg/dl) compared to VIA (137.3 ± 17.7 mg/dl) and WTR (140.2 ± 16.3 mg/dl). This peak was followed by the steepest quantitative decline for DCF in the second half of testing. (The non-significant interaction prevented post hoc statistical analyses). More robustly, an interaction ( P  ≤ 0.05) during incremental area under the curve analysis (AUC, mg/dl * min), when followed up by SNK post hoc testing, revealed that the peak AUC for DCF at 30–60 min. was 14.4% above baseline ( P  ≤ 0.05) and declined significantly at both the 60–90 segment and the 90–120 min segment (both P  ≤ 0.05). VIA induced an AUC peak at 30–60 min. 17.1% above baseline ( P  ≤ 0.05) with a less-steep decline by the 60–90 min. segment (NS) and the 90–120 min. segment ( P  ≤ 0.05). Comparatively, the WTR AUC peak of 15.6% did not decline significantly in later stages of the OGTT ( P  ≥ 0.05). Conclusions: These early data support the hypothesis, suggesting instant coffees, both decaffeinated and regularly caffeinated, cause a mild but observably greater glucose disposal compared to water during the late stages of an OGTT in young, healthy participants. Future research should include insulin measures to elucidate the benefits of coffee on glycemia in university students. Funding Sources: University of Mount Union Inter-Science Research Club.